Prevalence and molecular characterization of Enterocytozoon bieneusi in endangered Eld’s deer (Rucervus eldii) in Hainan, China - Yun Zhang; Yun Zhang; Guangxu Ren; Guangxu Ren; Qingqing Lu; Jiaqi Li; Jiaqi Li; Yu Qiang; Youyou Li; Xiuyi Lai; Yuan Wang; Xingyue Yu; et al. (Frontiers in Veterinary Science)
IntroductionEnterocytozoon bieneusi is one of the most frequent microsporidia species causing digestive disorder mainly diarrhea in humans and animals. Eld’s deer (Rucervus eldii) is the class I national key protected wildlife and only distributed on Hainan Island in China. No report on the prevalence and molecular characterization of E. bieneusi in wild Eld’s deer worldwide.Methods217 fecal samples were collected from Eld’s deer in two isolated habitats of a nature reserve in Hainan, and examined by nested Polymerase Chain Reaction (PCR) targeting the internal transcribed spacer (ITS) region.Results and discussionThe overall prevalence of E. bieneusi in Eld’s deer was 17.5% (38/217), with 13.5% (12/89) and 20.3% (26/128) in habitats 1 and 2, respectively. Seven ITS genotypes were identified, including five known genotypes: D (n = 19), Peru11 (n = 10), EbpC (n = 5), Peru8 (n = 1) and Type IV (n = 1), and two novel genotypes: HNED-I and HNED-II (one each). Genotypes Peru8 and Peru11 were firstly identified in cervids. Phylogenetic analysis showed that all the detected genotypes belonged to zoonotic Group 1. The results implied that the further research on threaten of E. bieneusi to endangered Eld’s deer and potential risks for public health is necessary.